2018
DOI: 10.1038/s41419-017-0039-y
|View full text |Cite
|
Sign up to set email alerts
|

Systems modeling accurately predicts responses to genotoxic agents and their synergism with BCL-2 inhibitors in triple negative breast cancer cells

Abstract: Triple negative breast cancer (TNBC) is an aggressive form of breast cancer which accounts for 15–20% of this disease and is currently treated with genotoxic chemotherapy. The BCL2 (B-cell lymphoma 2) family of proteins controls the process of mitochondrial outer membrane permeabilization (MOMP), which is required for the activation of the mitochondrial apoptosis pathway in response to genotoxic agents. We previously developed a deterministic systems model of BCL2 protein interactions, DR_MOMP that calculates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 43 publications
4
31
0
Order By: Relevance
“…These data suggest that BCL-2 might also control or correlate with cell proliferation, and that ABT-199 inhibits cell proliferation when administrated as a monotherapy (as also seen in ER-positive breast cancer [ 26 ]). This effect may be linked to the ability of BCL-2 to improve bioenergetics in cancer cells, which in turn would be inhibited by Bcl-2 and Bcl-xL antagonists [ 10 ]. However, we did not observe an inhibitory effect on cell proliferation in the combined treatment group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that BCL-2 might also control or correlate with cell proliferation, and that ABT-199 inhibits cell proliferation when administrated as a monotherapy (as also seen in ER-positive breast cancer [ 26 ]). This effect may be linked to the ability of BCL-2 to improve bioenergetics in cancer cells, which in turn would be inhibited by Bcl-2 and Bcl-xL antagonists [ 10 ]. However, we did not observe an inhibitory effect on cell proliferation in the combined treatment group.…”
Section: Discussionmentioning
confidence: 99%
“…It incorporates BCL-2 protein levels of five BCL-2 family members BAK, BAX, BCL-2, BCL-2-like 1-long (BCLxL), and myeloid leukaemia cell differentiation protein (MCL-1), measured by quantitative Western blotting or reverse phase protein array analysis, their interaction kinetics, as well as translocation and degradation kinetics of these proteins to calculate the amount of BH3-only proteins (‘stress dose’) required to induce the process of MOMP [ 7 , 9 ]. DR_MOMP hence delivers for each tumour/cell type a numerical value (‘stress dose’) that is a prognostic marker of clinical outcome in colorectal cancer (CRC) [ 7 , 8 , 9 ], and capable of predicting the response of CRC [ 7 ] and breast cancer cells [ 10 ] to genotoxic therapy. Here, we extended the application of DR_MOMP to include the effect of ABT-199 on the apoptosis signalling network, and to determine whether the deterministic model could also be used as a stratification tool for the BCL-2 antagonist ABT-199 in in vivo CRC patient derived xenograft (PDX) models ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Malignant lymphoid cell lines express different Bcl‐2 proteins in the order of 2000–200 000 molecules per cell . In colon carcinoma and triple negative breast cancer cells, the absolute concentrations ranged from low nanomolar to low micromolar protein concentrations . For a cellular volume of around 1 picoliter, this translates to roughly 1000–1 000 000 proteins per cell (Fig.…”
Section: What Are the Cellular Concentrations And Proapoptotic Threshmentioning
confidence: 99%
“…A promising treatment strategy thus is inducing activator expression and at the same time sensitizing cells by sequestering prosurvival Bcl‐2 family proteins. For instance, in triple negative breast cancer, cisplatin synergizes with the BH3‐mimetics ABT‐199 and WEHI‐539 . Chemotherapeutics in combination with the death receptor‐engaging ligand TRAIL (tumor necrosis factor‐related apoptosis‐inducing ligand) synergistically induce apoptosis in otherwise resistant liver tumor cells, and also primary hepatocytes, by engaging multiple proapoptotic Bcl‐2 family members .…”
Section: How Can We Exploit Our Quantitative Knowledge To Develop Effmentioning
confidence: 99%
“…However, little information is currently available whether selective inhibition of BCL2 or other anti-apoptotic BCL-2 protein such as BCL(X)L also influences mitochondrial function and energetics in cancer cells [ 21 ], and whether these functions can be exploited therapeutically. We have previously observed that treatment of triple negative breast cancer (TNBC) cells with Venetoclax or the selective BCL(X)L inhibitor WEHI-539 synergistically increased responses to the cytotoxic agent cisplatin, but that responses could not be fully explained by an increased sensitivity of the cells to undergo MOMP [ 22 ]. In the present study, we therefore explored whether selective BCL2 or BCL(X)L inhibition impacted on mitochondrial bioenergetics using a combined high content analysis and single-cell Foerster resonance energy transfer (FRET)-based imaging approach, and investigated how these effects related to cell death induction by BCL2 and BCL(X)L inhibitors.…”
Section: Introductionmentioning
confidence: 99%